Causes and Consequences of Medical Coding Errors: A Systematic Review of the Literature - As Salman, Mashail Salman; Almalki, Arwa Ahmed; Qadah, Amirah Ibrahim; Iqbal, Omniyah Hassan; Nasef, Hind Abdullah; Alharthi, Ahlam Awiad; Alqurashi, Sahar Mutair; Alharbi, Rana Malek; Almuqati, Rehab Saud; Alzahrani, Afaf Abdullah (Journal of Posthumanism, 2024)
Medical coding is necessary for proper record-keeping, billing, and managing health data, yet errors are still common because of organization, employees or staff and technology. These mistakes can have major effects on finances, patients and administration, which show how important it is to look into them in a comprehensive way. The objective of the research is to examine the causes and consequences of medical coding errors within the healthcare centers. Thorough A search of databases including Scopus, PsycINFO, and Web of Science to find and systematize studies that was published between 2020 and 2024. The criteria for inclusion in this research were English-language sources obtained from the specified search engines. The chosen research must also provide valuable insights into team dynamics and utilize established measuring scales. After an initial screening and quality assessment, Eleven studies were incorporated into the synthesis. On the basis of result, electronic databases to search the study database and found 34345 records. Eleven distinct records were evaluated for eligibility based on their titles and abstracts. Eleven studies were chosen for full-text review after the first screening. Eleven studies matched the criteria after an independent review and were included in the systematic review. The chosen investigations were carried out from 2020 to 2024 and exhibited diverse methodologies. The PRISMA flowchart shows how the selecting process works. Peer-reviewed journals, overall assessment, and quality management are all parts of quality evaluation. Findings revealed that medical coding errors arise from human, organizational, and technological factors, with serious consequences for patients, providers, and healthcare systems. Accurate coding is essential to safeguard patient safety, financial stability, and reliable health data for policymaking. Strengthening training, auditing, and technology integration can reduce errors and enhance healthcare quality, particularly within the Saudi Arabian context..